Relationship between the severity of carpal tunnel syndrome and lipid profile in patients with tip 2 diabetes mellitus - Aciman Demirel, Esra; Karpuz, Burcu; Açıkgöz, Mustafa; Atasoy, Hüsyin Tuğrul (Journal of Surgery and Medicine, 2021)
Background/Aim: Diabetes mellitus (DM) accelerates the development of neuropathy, and carpal tunnel syndrome (CTS) is the most common form of entrapment neuropathy. The pathogenesis of diabetic neuropathy is multifactorial with its vascular and metabolic factors. In this study, we aimed to evaluate the relationship among the electrophysiological severity of CTS, lipid profile and serum atherogenic index in patients with Type 2 DM. Methods: In this hospital-based retrospective cross-sectional study, we retrospectively evaluated 202 type 2 DM patients, who presented to the electrophysiology laboratory of Zonguldak Bulent Ecevit University Faculty of Medicine between 2016-2019 and investigated the relationship among the electrophysiological severity of CTS, lipid profile and serum atherogenic index of 131 patients diagnosed with CTS. Results: The patients with CTS had significantly higher values of fasting blood glucose and HbA1c compared to those without CTS (P=0.010). In terms of the severity of CTS, the patients were divided into three groups as mild, moderate, severe. In terms of the lipid panel, the mean values of cholesterol, triglyceride, and HDL-C were similar among the groups (P=0.098, P=0.321, P=0.706), while LDL-C levels were higher in the severe CTS group. (P=0.024). There was a significant positive correlation between age (R=0.126 P=0.004), HbA1c (R=0.245, P=0.002) and CTS severity. Conclusion: We identified a relationship between CTS severity and LDL-C. CTS should be considered in patients with DM and hyperlipidemia. Further larger-scale studies with control groups are recommended.